2002
DOI: 10.1128/jcm.40.3.480-489.2002
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Human Leptospirosis by Monoclonal Antibody-Based Antigen Detection in Urine

Abstract: Hybridomas secreting specific monoclonal antibodies (MAb) to all members of the genus Leptospira (clone LF9) and those that are specific only to the pathogenic species (clones LD5 and LE1) were produced. MAb LF9, which was immunoglobulin G1 (IgG1), reacted to a 38-kDa component of the sodium dodecyl sulfate-polyacrylamide gel electrophoresis-separated whole-cell lysates of all Leptospira spp., while MAb LD5 and MAb LE1, which were IgG1 and IgG2a, respectively, reacted to the 35-to 36-kDa components of all sero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 31 publications
2
36
0
4
Order By: Relevance
“…The addition of sucrose, which is known as a preservative and resolubilization agent (26), to the conjugate pad made the gold conjugate more stable and flow better. Even though the overall sensitivity and specificity of the ICG-based LFA are still Ͻ90%, they are still higher than those of the IgM dipstick assay (9), which is often used in an initial screening for leptospirosis. In summary, we have developed assays that can detect the presence of Leptospira antigen in the urine of humans and animals and can discriminate it from other bacterial antigens; however, this assay is not able to identify the infecting serovar of Leptospira.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The addition of sucrose, which is known as a preservative and resolubilization agent (26), to the conjugate pad made the gold conjugate more stable and flow better. Even though the overall sensitivity and specificity of the ICG-based LFA are still Ͻ90%, they are still higher than those of the IgM dipstick assay (9), which is often used in an initial screening for leptospirosis. In summary, we have developed assays that can detect the presence of Leptospira antigen in the urine of humans and animals and can discriminate it from other bacterial antigens; however, this assay is not able to identify the infecting serovar of Leptospira.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we tried to develop a rapid diagnostic assay (i.e., dipstick and ICG-based LFA) for leptospirosis which might fulfill these requirements and be applicable in all countries. Nowadays, the ICG assay for leptospirosis, which is used as one of the diagnostic methods, is mainly used for the detection of antibodies (9,33,34). However, these assays are difficult to use for early diagnosis because of their low sensitivities and the fact that the immune response might not have developed enough to be detected during the early stages of infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative PCR techniques, prognostically useful, have shown that higher leptospiral burden (> ~10 4-5 of leptospires/mL of blood) is associated with worse disease [4••,37,38]. Demonstration of the presence of Leptospira by antigen detection to diagnose leptospirosis is currently under development but it remains to be shown whether these antigen detection tests are sufficiently sensitive to diagnose disease caused by different infecting leptospiral strains [39,40].…”
Section: Diagnostic Microbiologymentioning
confidence: 99%
“…Immunochromatography based methods for detection of Leptospiral lipopolysaccharide antigen in urine have also been developed. 12 The sensitivity and specificity of these methods are often debatable due to prior exposure of the individuals in endemic areas and due to the contaminating nonpathogenic lectospires in the environment.…”
mentioning
confidence: 99%